2019
DOI: 10.1002/smll.201903952
|View full text |Cite
|
Sign up to set email alerts
|

Solid/Solid Interfacial Architecturing of Solid Polymer Electrolyte–Based All‐Solid‐State Lithium–Sulfur Batteries by Atomic Layer Deposition

Abstract: Solid polymer electrolytes (SPEs)-based all-solid-state lithium-sulfur batteries (ASSLSBs) have attracted extensive research attention due to their high energy density and safe operation, which provide potential solutions to the increasing need for harnessing higher energy densities. There is little progress made, however, in the development of ASSLSBs to improve simultaneously energy density and long-term cycling life, mostly due to the "shuttle effect" of lithium polysulfide intermediates in the SPEs and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 58 publications
1
53
0
Order By: Relevance
“…To inhibit polysulfide shuttle and improve the interfacial stability, researchers have added inorganic fillers in PEO‐based solid polymer electrolytes such as Al 2 O 3 , [ 184,209 ] SiO 2 , [ 210 ] ZrO 2 , [ 211 ] nanoclay, [ 212,213 ] and MOF. [ 214 ]…”
Section: Solid‐state Electrolytesmentioning
confidence: 99%
“…To inhibit polysulfide shuttle and improve the interfacial stability, researchers have added inorganic fillers in PEO‐based solid polymer electrolytes such as Al 2 O 3 , [ 184,209 ] SiO 2 , [ 210 ] ZrO 2 , [ 211 ] nanoclay, [ 212,213 ] and MOF. [ 214 ]…”
Section: Solid‐state Electrolytesmentioning
confidence: 99%
“…[63] In contrast, Liu et al reported that an active Li surface grafted with double-block polymer brushes (DPB) to form a high Li + -conductivity polymeric interfacial layer (Figure 11d), [43] while Fan et al coated Al 2 O 3 onto an electrolyte surface by atomic layer deposition (Figure 11e). [193] Additionally, a self-healing adaptive buffer layer (an ABL consisting of low molecular-weight polypropylene carbonate, PEO and Li salt) (Figure 11f) and Pt metal, by magnetron sputtering (Figure 11g), were also proposed to stabilize the Li anode/polymer electrolyte interface. [42,194] Clearly, stable interfaces between the Li anode and polymer electrolyte can be successfully achieved by creating protective layers on the surface of the electrolyte or Li anode before (e.g., deposition or polymerization) and during (e.g., reacting with additives in the electrolyte) battery operation.…”
Section: Anode/polymer Electrolytementioning
confidence: 99%
“…Reproduced with permission. [193] Copyright 2019, Wiley-VCH. f) The interface contact of Li/polymer electrolyte with or without ABL layer before and after electrochemical cycle.…”
Section: Introductionmentioning
confidence: 99%
“…For example, solid/solid interfacial architecturing through atomic layer deposition of Al 2 O 3 on the SPE surface could suppress the "shuttle effect" of lithium polysulde intermediates in the SPE and increase the interfacial compatibility between the metal lithium anode and the SPE. 189 Considering the unique advantages of SSEs, some perspectives presented herein are based on CSSEs.…”
Section: Discussionmentioning
confidence: 99%